GERMINATION, VIGOR AND SEED BIOMETRICS OF Licania kunthiana Hook.f. - Fernandes, Richard Matheus; Abreu, Clara Anne Araújo; Abreu, Bruno Carlos Feliciano de Lima; Oliveira, Ademir Kleber Morbeck (Floresta, 2021)
Licania kunthiana, popularly known as ‘fruta-de-morcego’, is a medium-size plant found in seasonal forest areas of the Amazon, Caatinga, Cerrado and the Atlantic Forest. The wood of the plant is used in civil construction and in the manufacture of furniture. However, the species lacks information concerning ideal conditions for germination and biometric characteristics of its seeds. In this manner, the current study aimed to investigate the germination potential, vigor (speed germination index - SGI and average germination time - AGT), initial growth (total length) and biometrics of L. kunthiana seeds. Constant (20, 25, 30 and 35 °C) and alternating (20-30 and 25-35 °C) temperatures were used, in a completely randomized design. The seeds had an average height of 1.7 cm, diameter of 1.4 cm and weight of 1.4 g, with a greater variation coefficient for length. The species shows better germination performance and formation of normal seedlings at temperatures of 25 and 30 °C, with results indicating that the vigor of the seeds can be considered high (25 °C - 2.2 SGI and 6.1 AGT; 30 °C - 1.9 SGI and 8.9 AGT). The relative frequency of germination indicated L. kunthiana seeds are not perfectly synchronized, displaying rapid germination over a short time period.